MicroRNA-10A* and MicroRNA-21 Modulate Endothelial Progenitor Cell Senescence Via Suppressing High-Mobility Group A2 - Zhu, Shoukang (2012)
RATIONALE: Endothelial progenitor cells (EPCs) contribute to the regeneration of endothelium. Aging-associated senescence results in reduced number and function of EPCs, potentially contributing to increased cardiac risk, reduced angiogenic capacity, and impaired cardiac repair effectiveness. The mechanisms underlying EPC senescence are unknown. Increasing evidence supports the role of microRNAs in regulating cellular senescence. OBJECTIVE: We aimed to determine whether microRNAs regulated EPC senescence and, if so, what the underlying mechanisms are. METHODS AND RESULTS: To map the microRNA/gene expression signatures of EPC senescence, we performed microRNA profiling and microarray analysis in lineage-negative bone marrow cells from young and aged wild-type and apolipoprotein E–deficient mice. We identified 2 microRNAs, microRNA-10A* (miR-10A*), and miR-21, and their common target gene Hmga2 as critical regulators for EPC senescence. Overexpression of miR-10A* and miR-21 in young EPCs suppressed Hmga2 expression, caused EPC senescence, as evidenced by senescence-associated β–galactosidase upregulation, decreased self-renewal potential, increased p16(Ink4a)/p19(Arf) expression, and resulted in impaired EPC angiogenesis in vitro and in vivo, resembling EPCs derived from aged mice. In contrast, suppression of miR-10A* and miR-21 in aged EPCs increased Hmga2 expression, rejuvenated EPCs, resulting in decreased senescence-associated β–galactosidase expression, increased self-renewal potential, decreased p16(Ink4a)/p19(Arf) expression, and improved EPC angiogenesis in vitro and in vivo. Importantly, these phenotypic changes were rescued by miRNA-resistant Hmga2 cDNA overexpression. CONCLUSIONS: miR-10A* and miR-21 regulate EPC senescence via suppressing Hmga2 expression and modulation of microRNAs may represent a potential therapeutic intervention in improving EPC-mediated angiogenesis and vascular repair.